Korelasi Proses Menghafal Al-Qur’an dengan Prestasi Belajar Siswa di MI Terpadu Tahfidzul Qur’an Al-Ma’shum Surakarta - Kinesti, Rakanita Dyah Ayu; Rahmawati, Siti Dewi; Ahsan, Wildani Nur; Ilfa, Yassir (ANWARUL, 2023)
The process of memorizing the Al-Qur'an is one of the processes of remembering, which can be said where all the contents in the components of the verse (parts and details such as signs of waqaf, washal, etc.) really need to be memorized perfectly. Among the benefits of memorizing the Al-Qur'an is increasing the strengthening ability of the brain in which the person must be careful and careful when distinguishing verses in the Al-Qur'an that have similarities in editorial. This study also aims to find out how the effect of memorizing the Koran on student achievement at the Integrated MI Tahfidzul Qur'an Al-Ma'shum Surakarta. The type of this research is a qualitative research. The data collection was carried out using documentation, observation sheets of memorizing the Al-Qur'an. The conclusion that can be obtained from this study is that there is a very positive and significant correlation between Al-Quran memorization and student achievement at the Integrated MI Tahfidzul Qur'an Al-Ma'shum Surakarta, with this it can be shown that student learning outcomes are being in school 40% is influenced by the ability of students and 60% is influenced by environmental factors.